2023
DOI: 10.1051/0004-6361/202243435
|View full text |Cite
|
Sign up to set email alerts
|

Time variability of the core-shift effect in the blazar 3C 454.3

Abstract: Measuring and inferring the key physical parameters of jets in active galactic nuclei (AGN) requires high-resolution very long baseline interferometry (VLBI) observations. Using VLBI to measure a core-shift effect is a common way of obtaining estimates of the jet magnetic field strength, a key parameter for understanding jet physics. The VLBI core is typically identified as the bright feature at the upstream end of the jet, and the position of this feature changes with the observed frequency, rcore ∝ ν−1/kr. D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
2
5
0
Order By: Relevance
“…However, k r measured in 2020 shows a larger deviation. The value of k r (lower than 1) and its change with time is very similar to the blazar 3C 454.3 studied by Chamani et al (2023), with wide multifrequency and multiepoch observations, who found the value of k r for 3C 454.3 varies between ∼1 and values lower than 1.…”
Section: | = Dsupporting
confidence: 80%
See 1 more Smart Citation
“…However, k r measured in 2020 shows a larger deviation. The value of k r (lower than 1) and its change with time is very similar to the blazar 3C 454.3 studied by Chamani et al (2023), with wide multifrequency and multiepoch observations, who found the value of k r for 3C 454.3 varies between ∼1 and values lower than 1.…”
Section: | = Dsupporting
confidence: 80%
“…for a given frequency pair) and OS is the difference of the core coordinates. The corresponding uncertainties were derived by using the method described in the study of Chamani et al (2021Chamani et al ( , 2023. In our study, the uncertainty of the core shift is estimated as…”
Section: | = Dmentioning
confidence: 99%
“…pattern (Sokolovsky et al 2011;Chamani et al 2023). In our VLBA observations, the C1 component at 5.5 and 8.5 GHz is core dominated.…”
Section: A Parsec-scale Jet or An Outflow?supporting
confidence: 45%
“…From the physical point of view, the high T B,int , especially close to the inverse-Compton limit, can be due to an increased number of energetic and emitting electrons, for instance due to strong particle acceleration by turbulence (e.g., Marscher 2014) or other mechanisms (see discussions in Kovalev et al 2016). The changing particle density can also cause significant variations in the nuclear opacity, as observed by time-variable shift of the VLBI core positions (Plavin et al 2019;Chamani et al 2023). We note that the arcsecond-scale core of M87 shows elevated X-ray flux density around 2014 (Sun et al 2018), which could be supporting evidence for higher T B,int in 2014 February than other epochs.…”
Section: Discussionmentioning
confidence: 99%